Exploring Discrimination and Mental Health Disparities Faced By Black Sexual Minority Women Using a Minority Stress Framework. (September 2015) - Calabrese, Sarah K.; Meyer, Ilan H.; Overstreet, Nicole M.; Haile, Rahwa; Hansen, Nathan B.
Black sexual minority women are triply marginalized due to their race, gender, and sexual orientation. We compared three dimensions of discrimination—frequency (regularity of occurrences), scope (number of types of discriminatory acts experienced), and number of bases (number of social statuses to which discrimination was attributed)—and self-reported mental health (depressive symptoms, psychological well-being, and social well-being) between 64 Black sexual minority women and each of two groups sharing two of three marginalized statuses: (a) 67 White sexual minority women and (b) 67 Black sexual minority men. Black sexual minority women reported greater discrimination frequency, scope, and number of bases and poorer psychological and social well-being than White sexual minority women and more discrimination bases, a higher level of depressive symptoms, and poorer social well-being than Black sexual minority men. We then tested and contrasted dimensions of discrimination as mediators between social status (race or gender) and mental health outcomes. Discrimination frequency and scope mediated the association between race and mental health, with a stronger effect via frequency among sexual minority women. Number of discrimination bases mediated the association between gender and mental health among Black sexual minorities. Future research and clinical practice would benefit from considering Black sexual minority women's mental health in a multidimensional minority stress context.